INFLUENCE OF L-ARGININ AND AMINOGUANIDINE ON RENAL FREE-RADICAL OXIDATION RATES IN CASES OF EXPERIMENTAL ANTIPHOSPOLIPID SYNDROME - Yaremchuk О.Z.; Posokhova, K.A.; Kulitska, M.I. (World of Medicine and Biology, 2018)
The aim of the study was to investigate the influence of L-arginine and aminoguanidine on the state of specific parameters of prooxidant-antioxidant system and renal tissue respiration in cases of experimental antiphospolipid syndrome and against the background of pregnancy in animals with this pathology. Antiphospolipid syndrome (APS) was modeled using BALB/c mice by means of cardiolipin according to the technique by Zaichenko H.V., et al (2011). It was established that in the presence of APS in kidneys, the imbalance in the system of antioxidant-antioxidants took place. The inhibition of membrane lipids peroxidation processes in kidneys of the animals with APS was evidenced in administration of L-arginine (25 mg/kg), and against the background of aminoguanidine (10 mg/kg) management its continued activation was proved. During the research on the 18th day of pregnancy in the kidneys of animals with APS the activation of free radical processes was evidenced, as well as simultaneous decrease of activity of antioxidant defence enzymes and mitochondria respiratory chain. The activation of renal antioxidant protection system in the animals with APS on the 18th day of pregnancy on the background of L-arginine administration was proved by the increase of activity of superoxide dismutase, catalase and reduced glutathione content compared to the pregnant mice with APS. The increased activity of succinate dehydrogenase and cytochrome oxidase was established. Against the background of aminoguanidine management in the presence of APS with underlying pregnancy, the intensification of free-radical oxidation, increase of catalase activity and reduced glutathione content was evidenced in kidneys. The administration of L-arginine in cases of APS with underlying pregnancy in the animals with APS was followed by the decrease of oxidative stress manifestations, specifically the decrease in lipid peroxidation level, reactivation and restitution of content of antioxidant system components and electron transport chain enzymes in kidneys. The aminoguanidine management in kidneys of animals with APS with underlying pregnancy was manifested by incoordination in prooxidant-antioxidant system in the animals with this pathology.